Episiotomia: a caracterização do estado de anomia dos direitos sexuais e humanos no momento do parto - Alves, Cândice Lisbôa (2023)
The objective of this article was to analyze the routine episiotomy as a form of institutional and sexual obstetric violence based on existing normative dispositions and the sexual culture of the society in order to ascertain a context of anomie and the tortuous character of the procedure. The method of inductive approach in the configuration of the episiotomy as an inhuman and degrading treatment was used, equating it to torture. The procedure method is the monographic one with the use of bibliographical and legislative research. As results, it was verified that the episiotomy is located in a context of anomia, since there are normative instruments that discourage its practice because it is a lesion in the perineum that violates sexual and human rights, and its unrestricted realization constitutes a violation of the Code of Medical Ethics. It is also contemplated that the episiotomy is a kind of torture, because it is subsumed in a context of mistreatment, offense to the corporal integrity, violation of the free disposition of the body, of the right to the information for the making of autonomous and informed decisions and to consent without coercion, in addition to sexual and human rights, ending discriminatory, demeaning and disrespectful treatment of women's sexual and human rights.